(3GdeMGSHI GdeJbOeI (B:s (3MGdGJ h JWHjbGJ YedjI aj GdeTGcd GdeMGSHjI GdeYGUQI (B/s - (3eWQ, eMeOs ((3YeGf(B: s (3OGQ hGFd(B, s, 2010)
(3GdGWGQ GdfXQj dGfOeGL GdTQcGJ , GdeMGSHI Yf YedjI GdGfOeGL HJGQjN MOhKgG h HfSHI Jedc cGedI h HfSHI Jedc ZjQ cGedI , GdeMGSHI Yf YedjI GdGfOeGL HYO MOhKgG , GdeMGSHI Yf YedjGJ GdHjY GdeJHGOdI aj eLGd GdHVGYI , GdeMGSHI Yf YedjGJ GdHjY GdeJjGOdI aj eLGd GdCUhd WhjdI GdGLd ,GdeMGSHI Yf GdYedjGJ GdeJHGOdI aj eLGd GdEbQGV , GdGWGQ GdfXQj ddeMGSHI Yf GdYedGJ GdGLfHjI , GdeMGSHI Yf aQhbGJ CSYGQ GdUQa GdfGJLI Yf YedjGJ Gh UabGJ JLGQjI JJe HGdYedI GdGLfHjI eZWGI h ZjQ eZWGI HYbhO UQa BLdI , GdeMGSHI Yf aQhbGJ CSYGQ GdUQa GdfGJLI Yf bQhV JJe HGdYedI GdGLfHjI , h GdfGJLI Yf JQLeI GdbhGFe GdeGdjI ddaQhY h GdTQcGJ GdCLfHjI , GdGWGQ GdfXQj deMGSHI YbhO GdGjLGQh GNjQG GdeMGSHI Yf YbhO GdGjLGQ(B.s
(3eQGLY U(B.419 (3; bGFeI GdeUWdMGJ U(B.413s
Keywords: (3GdeMGSHIs; (3JObjb GdMSGHGJ GdMchejIs